Molecular phylogeny of freshwater prawn (Genus: Macrobrachium) species based on mtDNA 168 rRNA gene sequencing - PARHI, JANMEJAY; LAKRA, W S; MAJUMDAR, K C; MUKHERJEE, S C; GOSWAMI, M; RAVINDER, K; SAHOO, L (The Indian Journal of Animal Sciences, 2011)
Molecular phylogeny of genus Macrobrachium was studied using 16S rRNA gene of mitochondrial DNA. The gene was amplified and sequenced to document the sequence variation between nine Macrobrachium species. Based on the phylogenetic investigation, M. rosenbergii, Mmalcolmsonii, M. gangeticum, M lamarrei and M. sankolii were grouped under one cluster and M. equidens, M. rude, M. idella and M. scabriculum formed a separate clade. Similarity indices between the sequences indicated maximum similarity between M. gangeticum and M. malcolmsonii and it was minimum between M. sankolii and M. rude. The hybridizable species including M. malcolmsonii, Mgangeticum and M. rosenbergii; are very close to each other. Â